2011
DOI: 10.1371/journal.pone.0020558
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Muscle Weakness in an Experimental Porcine Intensive Care Unit Model

Abstract: In critically ill patients, mechanisms underlying diaphragm muscle remodeling and resultant dysfunction contributing to weaning failure remain unclear. Ventilator-induced modifications as well as sepsis and administration of pharmacological agents such as corticosteroids and neuromuscular blocking agents may be involved. Thus, the objective of the present study was to examine how sepsis, systemic corticosteroid treatment (CS) and neuromuscular blocking agent administration (NMBA) aggravate ventilator-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 43 publications
2
56
1
1
Order By: Relevance
“…1). These results are in sharp contrast to our previous results in limb (biceps femoris) and respiratory (diaphragm) single muscle fibers in the same animals, showing an average 45% decline in specific force (48,50).…”
Section: Resultscontrasting
confidence: 99%
“…1). These results are in sharp contrast to our previous results in limb (biceps femoris) and respiratory (diaphragm) single muscle fibers in the same animals, showing an average 45% decline in specific force (48,50).…”
Section: Resultscontrasting
confidence: 99%
“…Numerous animal studies using a variety of species (mice, rats, rabbits, and pigs) have reported that prolonged MV results in significant atrophy of diaphragm muscle fibers (16,49,73,78,100,107). However, because the rat and human diaphragm are anatomically alike and contain a similar fiber type composition (76,81), the rat has become the most commonly used animal model to study MV-induced changes in diaphragm fiber size and function.…”
Section: Mv-induced Diaphragm Atrophymentioning
confidence: 99%
“…Moreover, prolonged MV also reduces rodent diaphragmatic-specific force production at submaximal stimulation frequencies (e.g., 10 -40 Hz) (56,73,87). Investigations using both rodent (113) and porcine (78) models indicate that MV-induced contractile dysfunction occurs in all muscle fiber types. This ventilator-induced impairment in diaphragmatic contractile function in animals appears to be directly linked to diaphragm contractile inactivity because ventilator modes that provide partial ventilator support or short periods of intermittent spontaneous breathing during prolonged MV can reduce the magnitude of full ventilator support-induced contractile dysfunction (35,44,49,94).…”
Section: Mv-induced Diaphragmatic Contractile Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forkhead box O (FOXO) family of transcription factors stimulates the expression of two important regulators of UPS-mediated proteolysis of ubiquitin ligase atrogin-1 and muscle-specific RING finger protein-1 (MuRF1) [63][64][65]. In animal models, both MuRF1 and atrogin-1 recruitment, and UPS activation, mainly contribute to the loss of muscle mass, such as inactivation-induced atrophy, acute illness, chronic disease, and CIM [63,66,67]. In human studies, mRNA expression levels of components of the UPS are increased in septic muscle.…”
Section: Early Phasementioning
confidence: 99%